Elucidation of anti-SARS-CoV-2 and anti-inflammatory bioactives in Qingyan Dropping Pills via integrated in silico screening and bioactivity validation - Liu, Liting; Li, Xinru; Wang, Xinyue; Zhang, Peng; Yang, Qi; Geng, Tong; Wang, Yuefei; Zhang, Junhua; Wang, Changjian; Yang, Jing; Zhang, Min (Frontiers in Medicine, 2025)
BackgroundThe global outbreak of coronavirus disease (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has raised significant public health concerns. Qingyan Dropping Pills (QDP), as a recommended drug, is issued by the National Health Commission of the People’s Republic of China for the treatment of COVID-19. However, its bioactive compounds and their mechanisms of action remain largely unidentified. In this study, the integration of computational and experimental approaches was performed to identify the bioactive compounds in QDP and elucidate its mechanisms against COVID-19.MethodsUtilizing UPLC-Q/TOF-MS, the chemical compounds of QDP were delineated, followed by network pharmacology analysis and molecular docking targeting SARS-CoV-2 spike protein (Spro), main protease (Mpro), and papain-like protease (PLpro). To validate the inhibitory activity of these compounds, fluorescence resonance energy transfer (FRET) and surface plasmon resonance (SPR) assays were employed. The antivival efficacy was tested in Vero E6 cells infected with SARS-CoV-2 Omicron BA.5 variant. Moreover, anti-inflammatory potential was evaluated via the measurement of inflammatory markers, including nitric oxide (NO), interleukin-6 (IL-6), interleukin-1 beta (IL-1β), and tumor necrosis factor-alpha (TNF-α).ResultsAmong the 48 identified compounds, 33 demonstrated potential antiviral activity against COVID-19. Notably, Hamamelitannin (HAM), corilagin (COR), and rhoifolin (RHO) effectively interacted with Spro, Mpro and PLproin silico. In SPR assays, the equilibrium dissociation constant (KD) for COR and RHO ranged from 4.515 × 10−8 M to 7.718 × 10−6 M, while HAM showed strong binding affinity to Spro (KD = 9.33 × 10−8 M) but weaker affinity for Mpro and PLpro. In FRET assays, COR and RHO inhibited Mpro with IC50 valuse of 0.73 μM and 21.61 μM, respectively. Additionally, COR proved effective against the Omicron BA.5 variant. The compounds COR, HAM, RHO, isoliquiritin (ISO), glycocholic acid (GLYCH), and gallic acid (GAL) displayed significant anti-inflammatory activity by inhibiting the crucial inflammatory factors, indicating their dual therapeutic potential in managing COVID-19.ConclusionOur study focused on Chinese patent medicine QDP to highlight the anti-SARS-CoV-2 and anti-inflammatory bioactives, providing evidence and insights into its clinical practice in the treatment of COVID-19.